2020
DOI: 10.2139/ssrn.3679026
|View full text |Cite
|
Sign up to set email alerts
|

Large Losses from Little Lies: Randomly Assigned Opportunity to Misrepresent Substantially Lowers Later Cooperation and Worsens Income Inequality

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Following the recent paper by Kim [38], we decide not to cluster the standard errors at the session level as doing so could produce false positive coefficients. Nonetheless, we have reported clustered standard errors in our pre-print version and the results are qualitatively the same [39].…”
Section: Plos Onementioning
confidence: 54%
“…Following the recent paper by Kim [38], we decide not to cluster the standard errors at the session level as doing so could produce false positive coefficients. Nonetheless, we have reported clustered standard errors in our pre-print version and the results are qualitatively the same [39].…”
Section: Plos Onementioning
confidence: 54%
“…Misrepresentation is a common PPBs, and has been studied the mechanism in economics and marketing [21][22][23][24][25]. Church et al [21] discussed the mechanism that how competition and altruism impact online disclosure behaviors considering user misrepresentation.…”
Section: Consumers' Privacy Protection Behaviours (Ppbs)mentioning
confidence: 99%
“…Church et al [21] discussed the mechanism that how competition and altruism impact online disclosure behaviors considering user misrepresentation. Drouvelis et al [22] found that consumers' misrepresentation may result in large losses. Kumar et al [24] concluded that the internet makes it easy for people to misrepresent their privacy information.…”
Section: Consumers' Privacy Protection Behaviours (Ppbs)mentioning
confidence: 99%
“…Misrepresentation is a common intentional PPB, which enables the consumer to take control of their private information [18,23,24]. Its mechanism has been studied by economics and marketing scholars [22,[25][26][27][28]. Kumar et al [28] have concluded that the Internet makes it easy for people to misrepresent their private information.…”
Section: Consumer Privacy Protection Behaviors (Ppbs)mentioning
confidence: 99%
“…Church et al [25] discussed the mechanism through which competition and altruism impact online disclosure behaviors considering user misrepresentation, and found that consumers are less likely to misrepresent if they are altruistic, in which case the firms may benefit. On the other hand, Drouvelis et al [26] found that misrepresentation may result in large losses, as misrepresentation makes marketing methods less effective. Zhou et al [29] constructed a model and found that misrepresentation leads to data noise and service failures, thus hurting both firms and consumers.…”
Section: Consumer Privacy Protection Behaviors (Ppbs)mentioning
confidence: 99%